Radiation and multiple slip effects on magnetohydrodynamic bioconvection flow of micropolar based nanofluid over a stretching surface - Abdal, Sohaib (2021)
Our aim in this article is to study the radiation and multiple slip effects on magnetohydrodynamic bioconvection flow of micropolar based nanofluid over a stretching surface. In addition, a steering mechanism of making improvements to the Brownian motion and thermophoresis motion of nanoparticles is integrated. The numerical solution of 2-dimensional laminar bioconvective boundary layer flow of micropolar based nanofluids is presented. The basic formulation as partial differential equations is transmuted into ordinary differential equations with the help of suitable similarity transformations. Which are then solved by using the Runge–Kutta method of fourth-order with shooting technique. Some important and relevant characteristics of physical quantities are evaluated via inclusive numerical computations. The influence of vital parameters such as buoyancy parameter λ, bioconvection Rayleigh number Rb, the material parameter K are examined. This investigation showed that with the increment in material parameter, micro rotation and velocity profile increases. In addition, the temperature rises due to the enhancement in Nb (Brownian motion) and Nt (thermophoresis parameter).